Auditory-somatosensory multisensory interactions are spatially modulated by stimulated body surface and acoustic spectra. - Tajadura-Jiménez, A; Kitagawa, N; Väljamäe, A; Zampini, M; Murray, M; Spence, C (2009)
Previous research has provided inconsistent results regarding the spatial modulation of auditory-somatosensory interactions. The present study reports three experiments designed to investigate the nature of these interactions in the space close to the head. Human participants made speeded detection responses to unimodal auditory, somatosensory, or simultaneous auditory-somatosensory stimuli. In Experiment 1, electrocutaneous stimuli were presented to either earlobe, while auditory stimuli were presented from the same versus opposite sides, and from one of two distances (20 vs. 70 cm) from the participant's head. The results demonstrated a spatial modulation of auditory-somatosensory interactions when auditory stimuli were presented from close to the head. In Experiment 2, electrocutaneous stimuli were delivered to the hands, which were placed either close to or far from the head, while the auditory stimuli were again presented at one of two distances. The results revealed that the spatial modulation observed in Experiment 1 was specific to the particular body part stimulated (head) rather than to the region of space (i.e. around the head) where the stimuli were presented. The results of Experiment 3 demonstrate that sounds that contain high-frequency components are particularly effective in eliciting this auditory-somatosensory spatial effect. Taken together, these findings help to resolve inconsistencies in the previous literature and suggest that auditory-somatosensory multisensory integration is modulated by the stimulated body surface and acoustic spectra of the stimuli presented.